Mengapa Jepang Memilih Hadratussyaikh: Analisa Sejarah Ditunjuknya KH. Hasyim Asy’ari Menjadi Ketua Masyumi - Muhammad As'ad (Tebuireng: Journal of Islamic Studies and Society, 2020)
This article seeks to answer why the Japanese chose KH. Hasyim Asy’ari as the chairman of Masyumi during their occupation in Indonesia (1942-1945). The data was collected from library research by scrutinizing paper and academic works that discuss Indonesia from the 1920s to its independence in 1945. This period is important to understand the historical and political conditions of the country at that time. This article also refers to two magazines of Suara MIAI that began publishing in December 1942 and Suara Masyumi Magazine issued from December 1943 onward. This article argues that the Japanese decision to choose Hadratussyaikh was based on political motivation, especially to get the support of the Muslim community for Japanese efforts to fight Allied forces in the Pacific war.